Faktor-Faktor yang Mempengaruhi Perilaku Minum Obat Tuberkulosis - Deny Novani; Agus Suwandono; Djoko Trihadi; M. Sakundarno Adi; Ari Suwondo (Dian Nuswantoro Semarang, 2017)
The Multi Drug Resistance Tuberculosis (MDR TB) is tuberculosis resistance to minimum of two very potent TB drugs, Isoniazid and Rifampicin. Non-adherence to TB treatment may result in development of MDR TB. The study objective is to assess the risk factors of non-adherence to TB-treatment among MDR TB patients.This was the case control study, while case were non-adhere patients (n=57), and control were patients who are adhere to treatment (n=91). Total samples were 148 patients, with 10% of those who have risk Data was analyzed using bivariate analysis with Chi Square test, Odds Ratio (OR) and multivariate with logistic regression. There are two variables found as risk factors of non-adherence to TB treatment among MDRTB patients; treatment history (p=0,014; OR:2,648; 95%CI:1,215-5,771), duration of treatment (p=0,008; OR:2,960; 95% CI:1,320-6,638). Probability of non-adherence when there are thesetwo factors is 52,99%. Treatment history and duration of treatment were found as risk factors of non-adherence to TB treatment among MDR-TB patients in this study.Keywords: Risk factors, non-adherence to treatment, development of MDR TB